Chromatic dispersion based wide-band, fiber-coupled, tunable light source for hyperspectral imaging - Sharma, Gargi; Naveed, Sheeza Kainat; Parmar, Asha; Singh, Kanwarpal (IEEE Access, 2021)
Hyperspectral imaging is a powerful label-free imaging technique that provides topological and spectral information at once. In this work, we have designed and characterized a hyperspectral source based on the chromatic dispersion property of off-the-shelf lenses and converted a supercontinuum laser light source into a hyperspectral imaging light source for 490 nm to 900 nm wavelength range with a spectral resolution of 3.5 nm to 18 nm respectively. The potential of the source was demonstrated by imaging two color dots with different absorption bands. Further, we generated the hypercube of the lily ovary and dense connective tissue and measured their spectral signature as a function of wavelength. We also imaged the lower tongue of a healthy volunteer at 540 nm, 630 nm, and white light. Our simple hyperspectral light source design can easily be incorporated in a standard endoscope or microscope to perform hyperspectral imaging.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Biomedical optical imaging; Broadband communication; Chromatic dispersion; Hyperspectral imaging; Hyperspectral imaging; Imaging; Lenses; Light sources; Light sources; Liquid crystals; Microscopy; Spectroscopy